The economic content of tax capacity in Uzbekistan and its role and significance in the tax system - Jurayev Xusan Atamuratovich (Genius Journals, 2026)
This article discusses the economic content of tax capacity, the laws of its formation and its strategic role in the tax system. During the study, the factors affecting tax capacity were analyzed and the importance of this indicator in stabilizing state budget revenues was substantiated. Also, ways to ensure the country's economic growth by expanding the tax base and increasing tax collection were considered. The article is intended for specialists interested in improving tax policy and optimizing the tax burden
Keywords: tax capacity; tax system; economic content